Innovative Strategy to Disseminate Science Information to Policy Makers - Azmi Hassan (STI Policy and Management Journal, 2019)
There exist a huge gap between science and technology discovery and the formulation of public policy mostly due to the poor understanding on how to disseminate the news not only to policy makers but also to the general public. There has been an outright explosion of new knowledge and no one person can know it all. To bring accurate, relevant information from the front lines of research to the policy makers, this paper will describe an innovative strategies that uses the media as the conduit. But with this approach, the critical pre-requisite is that the researcher and media must be able to work with each other and as the author found, this does not always come easily. This impasse will result in public policy formulated will not taking any account of new discoveries especially in science and technology field. It is hoped that by employing the ideas put forward, scientific and technology discoveries will be applied when formulating public policies in a more systematic ways. Keywords: science discovery, public policy, dissemination.